Analisis Proses Pembelajaran PAI sebagai Sarana Peningkatan Profil Pelajar Pancasila - Metha Nahda Afriliya; Asep Dudi Suhardini; Mujahid Rayid (UNISBA Press, 2024)
Abstract. This research focuses on changes to the education curriculum in Indonesia, especially in the context of the Independent Curriculum as a response to the impact of the Covid-19 pandemic. The Merdeka Curriculum introduces a new paradigm in the world of education by emphasizing new ideas about the learning process. One of the main elements in this curriculum is the Pancasila Student Profile which includes six important dimensions: faith, devotion to God Almighty, global diversity, mutual cooperation, creativity, critical and independent. The importance of religious education, especially Islamic Religious Education (PAI) as an integral part of the curriculum, can be seen from its aim to increase students' understanding, faith, appreciation and experience of Islamic teachings. This research was conducted at SMAN 1 Parungkuda Sukabumi using a qualitative approach and descriptive methods, with data collection techniques in the form of interviews, observation and documentation studies.The results of the research show that the process of planning and implementing PAI learning in class XI of SMAN 1 Parungkuda is in accordance with the applicable curriculum. Learning evaluation is carried out regularly and in a structured manner. The impact of the PAI learning process includes improving student character as recorded in education report cards.Supporting factors for the PAI learning process as a means of increasing the profile of Pancasila students include learning materials that cover the dimensions of the Pancasila student profile, as well as the presence of teachers who have an Islamic PAI undergraduate background. However, the inhibiting factors include differences in views in interpreting the results of the process of increasing the profile of Pancasila students. Thus, this research provides in-depth insight into the implementation of the Merdeka Curriculum and the role of Islamic Religious Education in raising the profile of Pancasila students at the high school level). Abstrak. Penelitian ini bermula pada perubahan kurikulum pendidikan di Indonesia, terutama dalam konteks Kurikulum Merdeka sebagai pemulihan terhadap dampak pandemi Covid-19. Kurikulum Merdeka memperkenalkan paradigma baru dalam dunia pendidikan dengan menekankan gagasan baru tentang proses pembelajaran. Salah satu elemen utama dalam kurikulum ini adalah profil pelajar pancasila, yang mencakup enam dimensi penting: keberiman, bertakwa kepada Tuhan Yang Maha Esa, berkebhinekaan global, gotong royong, kreatif, kritis, dan mandiri.Pentingnya pendidikan agama, khususnya Pendidikan Agama Islam (PAI), sebagai bagian integral dari kurikulum, tampak dari tujuannya untuk meningkatkan pemahaman, keimanan, penghayatan, dan pengalaman siswa terhadap ajaran Islam. Penelitian ini dilakukan di SMAN 1 Parungkuda Sukabumi menggunakan pendekatan kualitatif dan metode deskriptif, dengan teknik pengumpulan data berupa wawancara, observasi, dan studi dokumentasi.Hasil penelitian menunjukkan bahwa proses perencanaan dan pelaksanaan pembelajaran PAI di kelas XI SMAN 1 Parungkuda sesuai dengan kurikulum yang berlaku. Evaluasi pembelajaran dilakukan secara berkala dan terstruktur. Dampak dari proses pembelajaran PAI mencakup peningkatan karakter siswa yang tercatat dalam rapor pendidikan.Faktor pendukung proses pembelajaran PAI sebagai sarana peningkatan profil siswa Pancasila melibatkan materi pembelajaran yang mencakup dimensi profil siswa Pancasila, serta keberadaan guru dengan latar belakang sarjana PAI. Namun, faktor penghambat mencakup perbedaan pandangan dalam memaknai hasil dari proses peningkatan profil pelajar Pancasila. Dengan demikian, penelitian ini memberikan wawasan mendalam tentang implementasi Kurikulum Merdeka dan peran Pendidikan Agama Islam dalam meningkatkan profil siswa Pancasila di tingkat sekolah menengah atas.